Assessment of heavy metals pollution in sediment at the Omaruru River basin in Erongo region, Namibia. Issue 1 (1st January 2020) - Onjefu, Sylvanus Ameh; Shaningwa, Fatima; Lusilao, Julien; Abah, James; Hess, Euodia; Kwaambwa, Habauka Majority
ABSTRACT: This study determined the contamination levels of some heavy metals: Mn, Cr, Cu, Ni, Fe, As, and Al obtained from the delta basin of Omaruru River, using Inductively Coupled Plasma-Optical Emission Spectrophotometer (Optima 8000, Perkin Elmer). Chemical analysis showed that the sediments samples have metal concentrations ranging from 88 to 128mg/kg for Mn, 3973 to 4369mg/kg for Fe, 96 to 107mg/kg for Cr, 6 to 9mg/kg for Cu, 9 to 11mg/kg for Ni, 17 to 19mg/kg for As, and 11750 to 9002mg/kg for Al. The concentrations of Cr and As showed suggest that the sediment samples were heavily polluted according to United States Environmental Protection Agency's regulatory guidelines of the heavy metals. Additionally, the concentrations of Cr and As in the sediments exceeded the effect low range, effect medium range, threshold effect level, and the probable effect level proposed by the Canadian Council of Ministers of the Environment.